2013
DOI: 10.1007/s00268-013-2087-5
|View full text |Cite
|
Sign up to set email alerts
|

Early Enteral Nutrition Prevents Intra‐abdominal Hypertension and Reduces the Severity of Severe Acute Pancreatitis Compared with Delayed Enteral Nutrition: A Prospective Pilot Study

Abstract: Early enteral nutrition did not increase IAP. In contrast, it might prevent the development of IAH. In addition, EEN might be not appropriate during the initial 3-4 days of SAP onset. Moreover, EN might be of benefit to patients with an IAP <15 mmHg. Early enteral nutrition could improve disease severity and clinical outcome, but did not decrease mortality of SAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 52 publications
0
34
1
1
Order By: Relevance
“…Rationale: The improved outcome in moderate to severe acute pancreatitis with early EN is based primarily on studies comparing EN with PN, and PN in such cases may be a negative control. Limited support comes from studies showing benefit (trend toward reduced mortality) from early EN compared with STD 338 340 and improved outcomes from early EN (reduced infection, organ failure, ICU LOS, and SIRS) versus delayed EN 341 , 342 . What is not known is what percentage of patients with moderate to severe acute pancreatitis would tolerate advancing to oral diet (similar to the data on patients with mild disease) within 3–4 days from the time of admission and thus not need specialized nutrition therapy.…”
Section: Acute Pancreatitismentioning
confidence: 99%
“…Rationale: The improved outcome in moderate to severe acute pancreatitis with early EN is based primarily on studies comparing EN with PN, and PN in such cases may be a negative control. Limited support comes from studies showing benefit (trend toward reduced mortality) from early EN compared with STD 338 340 and improved outcomes from early EN (reduced infection, organ failure, ICU LOS, and SIRS) versus delayed EN 341 , 342 . What is not known is what percentage of patients with moderate to severe acute pancreatitis would tolerate advancing to oral diet (similar to the data on patients with mild disease) within 3–4 days from the time of admission and thus not need specialized nutrition therapy.…”
Section: Acute Pancreatitismentioning
confidence: 99%
“…Patients with moderate to severe acute pancreatitis refuse oral feeding due to nausea, vomiting and abdominal pain secondary to gastric stasis and abdominal distention following pancreas in ammation. Food intolerance is also present in early enteral nutrition 17 .…”
Section: Discussionmentioning
confidence: 99%
“…[35] In addition, early EN (<48 h) was found to have a protective effect against the development of intra-abdominal hypertension in SAP. [36] A recent meta-analysis revealed that NG was equivalent to NJ feeding in terms of mortality (relative risk [RR] = 0.69), risk of aspiration (RR = 0.46), exacerbation of pain (RR = 0.94), and achieving nutritional targets ( P = 0.97). [3437] At our center, we attempt to initiate NG feeds within 48 h of admission.…”
Section: Nutrition In Acute Pancreatitismentioning
confidence: 99%